DIAGRAM OF CRYSTAL-ORDERING IN TOURMALINE BASED ON X-RAY DIFFRACTION DATA - Afonina G.G.; Makagon V.M. (My University, 1990)
In calculating the structural formula of tourmaline, which has the general form XY3Z6B3Si6O27(O, OH, F)4, position Z is usually occupied by aluminum, position Y predominantly by Fe2+, Mg, Al + Li, Mn, Fe3+, and position X by Na and Ca. This type of structural formula reflects the ordering of tourmaline structure: Z-octahedra filled by Al and Y-octahedra by larger cations. Analysis of the infrared spectral lines of real crystals has demonstrated differing degrees of ordering of distribution of the different cations in the indicated positions. Our proposed dY-dZ diagram enables us to determine the degree of ordering (in relative terms) in tourmaline structure, using powder diffraction diagrams. It also helps to estimate the approximate composition and possible distribution of cations in the Y and Z positions in the tourmaline structure.